2013
DOI: 10.1007/s11999-013-3055-y
|View full text |Cite
|
Sign up to set email alerts
|

How Useful Is MRI in Diagnosing Isolated Bundle ACL Injuries?

Abstract: Background Selective bundle anterior cruciate ligament (ACL) reconstruction and/or remnant ACL preservation may be reasonable options for some patients. However, the frequency of isolated anteromedial (AM) or posterolateral (PL) bundle injuries in patients undergoing ACL reconstruction is unknown, and the value of MRI for prediction of this injury pattern is likewise unknown. Questions/purposes We sought to determine (1) the proportion of knees with an intact AM or PL bundle in patients undergoing ACL reconstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…A study done by Lawrence et al, [12] showed that MRI accurately diagnosed only one of nine partial ACL tears confirmed by arthroscopy [12] . However in another study done by Chang et al, [13] showed overall diagnostic accuracy of MRI in partial tears of 83% [13] .…”
Section: Discussionmentioning
confidence: 94%
“…A study done by Lawrence et al, [12] showed that MRI accurately diagnosed only one of nine partial ACL tears confirmed by arthroscopy [12] . However in another study done by Chang et al, [13] showed overall diagnostic accuracy of MRI in partial tears of 83% [13] .…”
Section: Discussionmentioning
confidence: 94%
“…MRI is highly sensitive and specific for the diagnosis of ACL injuries, 25 its usefulness with respect to the remnant tissue is controversial. Although a previous report suggests that diagnostic preoperative MRI provides limited information about the remnant tissue, 26 other researchers describe MRI as an important tool for predicting patterns of ACL remnant tissues 10 or bundle injuries with satisfactory precision. 26 In this study, MRI findings and videos of arthroscopic assessments were used to evaluate the remnant tissue volume, continuity, and tension.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 However, despite recent interest in ACL reconstruction with remnant tissue preservation, 18,20 there is limited information about the diagnostic values of preoperative MRI for the remnant tissue. 31 Normal ACL appears as a band comprising low signal lines, 32 while injured ACL gives a high signal in the MRI, which indicates fluid and hemorrhage confined to the intact synovial sheath. 33,34 Additionally, there is a report that MRI is also considered to be an important tool for predicting the pattern of ACL remnant tissue or bundle injury pattern with satisfactory precision.…”
Section: Discussionmentioning
confidence: 99%